Chimtou, Tunesien - von Rummel, Philipp (e-Forschungsberichte des DAI, 2023)
Ancient Simitthus (today Chimtou, Tunisia), known for its important quarries of yellow Numidian marble, has been the object of archaeological research conducted jointly by the Tunisian National Heritage Institute and the German Archaeological Institute in Rome since 1965. This report presents a short overview on the recent activities at Chimtou in 2012 and 2013, which were primarily dedicated to publishing the results of the excavations conducted in the 1980s northeast of the forum of the Roman town and the ‚temple of Imperial cult‘ accompanied by measures of capacity building and site management.